(untitled) (Proceedings of Scientific Conference on Multidisciplinary Studies, 2024)
The article explores the significance of the terminological system as the primary element of sector-specific language, which supports various areas of specialized human activities by fulfilling its cognitive role. It primarily focuses on analyzing distinctions between two potential sets of terms within industrial sublanguage: terminology and nomenclature.